1976
DOI: 10.1128/aac.10.4.639
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antibiotic Resistance in Clinical Strains of Neisseria gonorrhoeae Isolated in South Carolina

Abstract: Minimal inhibitory concentration (MIC) values for penicillin G, tetracycline, amoxicillin, and actinomycin D were determined for 81 strains of Neisseria gonorrhoeae isolated from patients attending public health clinics in the Piedmont region of South Carolina. Gonococcal isolates were also screened for highlevel resistance to streptomycin. Significant positive correlations (r -0.45, P c 0.01) were found between all possible pairs of the antibiotics penicillin G, tetracycline, and amoxicillin. The MIC values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although penicillin is still the best antibiotic, in recent years an increasing number of isolates of N. gonorrhoeae have become resistant to this agent (6,7,9,12,16). The basis of this resistance can be due to either a chromosomally mediated decrease in penicillin uptake by the bacteria (13) or the production of ,8-lactamase (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although penicillin is still the best antibiotic, in recent years an increasing number of isolates of N. gonorrhoeae have become resistant to this agent (6,7,9,12,16). The basis of this resistance can be due to either a chromosomally mediated decrease in penicillin uptake by the bacteria (13) or the production of ,8-lactamase (15).…”
mentioning
confidence: 99%
“…Although penicillin is still the best antibiotic, in recent years an increasing number of isolates of N. gonorrhoeae have become resistant to this agent (6,7,9,12,16 We have previously reported that HR 756, a new cephalosporin antibiotic, was very active against both gram-positive and gram-negative bacteria (14). In addition Fu and Neu (4) have shown that HR 756 was not hydrolyzed by the Richmond types I, III, IV, and V ,B-lactamases.…”
mentioning
confidence: 99%
“…It has been reported (Robson and Salit, 1972;Stolz et al, 1975;Watko and Brownlow, 1975;Meheus et al, 1976;Powell and Bond, 1976) that sensitivity to penicillin is highly correlated with sensitivity to ampicillin, tetracycline, and cephaloridine. The results of this study also show this correlation.…”
Section: Resultsmentioning
confidence: 99%